Use of plant extracts to control activities of the invasive giant African land snail Achatina fulica - Magar, Rubina Thapa; Sharma, Hari Prasad; Sharma, Sandhya; Belant, Jerrold L. (Geographical Journal of Nepal, 2023)
Giant African land snails (Achatina fulica; GALS) are a highly invasive herbivore and pose serious threats to native species and that could disrupt ecosystems. Various botanical extracts have been used as molluscicides to control mollusks for pest management. We aimed to identify the effects of neem (Azadirachta indica) and titepati (Artemisia vulgaris) to reduce GALS activities and survival using solutions of fresh neem leaf and titepati leaf, bark, and root. We found a fast movement in the GALS only in the extraction groups while the lethargic movement was lower in mulching method. A significant association of control groups with different extraction groups along with mulching treatment (p<0.05) however, no differences were observed among different extractions at 2.5% and 5% concentrations. Among the treatments, Neem leaf at 5% concentration was found to be effective as it helped immobilize the samples after ten days whilst other treatments required minimum 14 days to be effective. We recommend further studies of titepati and neem as control agents to reduce crop and vegetable damage from GALS.